Understanding data use and preference of data visualization for public health professionals: A qualitative study. Issue 4 (10th February 2021) - Park, Seungeun; Bekemeier, Betty; Flaxman, Abraham D.
Abstract: Objective: This study aimed to assess public health professionals' use of data, information, and evidence and to understand perceptions and preferences regarding data visualization to inform future design of data visualization tools. Design: We conducted qualitative interviews with public health professionals who use data for decision making as part of community health assessment and program planning from state and local health departments across six states. Results: We identified four themes: 1) collection of data, information, and evidence; 2) management and analysis of data and information to inform decisions; 3) use of data to support public health practice; and 4) preferences for data visualization and how visualization is being used. Public health professionals use data, information, and evidence from various resources for communicating with co‐workers, stakeholders, and the public, and decision making regarding their programs and services. Conclusion: Data visualization tools can help public health professionals improve their understanding and communication, their education of stakeholders, and their decision making using data, information, and evidence. Public health professionals believe in the value of using data, information, and evidence. Opportunities exist in ways to support public health professionals' data use by adopting data visualization tools and by mitigating systematic challenges in public health information systems.